2022
DOI: 10.28982/josam.938799
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiographic measurements of the wrist in the Turkish population

Abstract: Background/Aim: Wrist parameters measured on direct radiography are essential in diagnosing distal radius fractures and many specific wrist disorders and determining prognosis after treatment. Previous studies have shown the intercommunity variability of these parameters in the literature. To our knowledge, no study in the literature reflects the normal values in the Turkish population. This study aimed to determine the distribution and normal limits of parameters measured in posteroanterior (PA) and direct la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
(71 reference statements)
3
4
0
1
Order By: Relevance
“…Our study demonstrated the average third metacarpal length (mm) to be 62.4 ± 6.1 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 Our study demonstrated mean carpal height (mm) to be 32.4 ± 0.3 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 Our study demonstrated capitate length to be 22.3 ± 2.3 which was comparable to various studies in the literature ( Table 4 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study demonstrated the average third metacarpal length (mm) to be 62.4 ± 6.1 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 Our study demonstrated mean carpal height (mm) to be 32.4 ± 0.3 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 Our study demonstrated capitate length to be 22.3 ± 2.3 which was comparable to various studies in the literature ( Table 4 ).…”
Section: Discussionsupporting
confidence: 81%
“…12 13 14 15 16 Our study demonstrated mean carpal height (mm) to be 32.4 ± 0.3 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 Our study demonstrated capitate length to be 22.3 ± 2.3 which was comparable to various studies in the literature ( Table 4 ). 12 13 14 15 16 In the studies conducted by Tang et al, 17 Jafari et al, 12 and Vaezi et al, 13 males exhibited significantly greater carpal height, third metacarpal height, and capitate length compared to females.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Feipel ve ark. ise 80 el bileği radyografisini incelemiş ve ortalama RA ölçümünü 25°, UV ölçümünü ise -0,3 mm olarak elde etmişlerdir (21). Türk popülasyonundaki el bileği radyografilerinde ölçülen parametrelerin normal sınırlarını belirlemeyi amaçlayan Yalçın ve Polat'ın çalışmasında, RA, LFA ve UV ölçümlerinin ortalama değerlerini sırasıyla; 24,14°, 10,85° ve -0,08 mm olarak bulmuşlardır.…”
Section: Discussionunclassified
“…9 Several studies on a normal database of posterior-anterior (PA) radiographic wrist measurements are not exclusive to scaphoid-related parameters. 10,11 There have only been a few studies on normative data for the scaphoid, which are mainly computed tomography (CT)-based. 12 There is no normal morphometric radiography database of the scaphoid in a representative sample of the Indian population.…”
Section: Introductionmentioning
confidence: 99%